2019
DOI: 10.3389/fchem.2019.00384
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ozonation of Recalcitrant Organic Chemicals in Water Using Vanadium Oxides Loaded ZSM-5 Zeolites

Abstract: The discharge of wastewater having recalcitrant chemical compositions can have significant and adverse environmental effects. The present study investigates the application of a catalytic ozonation treatment for the removal of recalcitrant organic chemicals (ROCs) from the water. Novel catalytic materials using vanadium (V) oxides deposited onto the surface of NaZSM-5 zeolites (V/ZSM) were found to be highly efficient for this purpose. The highly-dispersed V oxides (V 4+ and V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Also, a wide range of zeolites, alone or modified by addition of metal oxides have been found to be efficient for pollutant removal by catalytic ozonation, due to a combination of parameters, including their high surface area, the possibility of adjusting hydrophilicity/hydrophobicity, the acidity by the silica to alumina ratio and the pore size. Metals, in the metallic state, supported on metal oxides are also active catalysts for ozonation by either favoring the production of •OH and/or the adsorption of the organic pollutant 32 . Some examples of the reaction mechanisms will be detailed in paragraph 2.2.…”
Section: Ozonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a wide range of zeolites, alone or modified by addition of metal oxides have been found to be efficient for pollutant removal by catalytic ozonation, due to a combination of parameters, including their high surface area, the possibility of adjusting hydrophilicity/hydrophobicity, the acidity by the silica to alumina ratio and the pore size. Metals, in the metallic state, supported on metal oxides are also active catalysts for ozonation by either favoring the production of •OH and/or the adsorption of the organic pollutant 32 . Some examples of the reaction mechanisms will be detailed in paragraph 2.2.…”
Section: Ozonationmentioning
confidence: 99%
“…Metals, in the metallic state, supported on metal oxides are also active catalysts for ozonation by either favoring the production of • OH or the adsorption of the organic pollutant. 32 Some examples of the reaction mechanisms will be detailed in section 2.2. Basically there are three types of mechanisms to explain the interaction of the catalyst with organic pollutants and O 3 :…”
Section: From Kinetics and Reaction Mechanisms To Reactor Design In C...mentioning
confidence: 99%
“…The evaluation of adsorption capacity, regarding a solid catalyst, is considered as very important in the catalytic ozonation process, due to the following reasons: (1) research studies have shown that heterogeneous catalytic ozonation is a synergistic process, during which, adsorption may also contribute via the improved contact between the pollutant and the catalyst (Valdés et al 2012;Shahamat et al 2014), and (2) a solid material can be characterized as catalyst when the efficiency of the catalytic system is higher than the efficiencies' sum of adsorption and of single ozonation (Xu et al 2019); i.e., the solid material should act mainly as a catalyst and not as an adsorbent agent. Table 2 shows the adsorption capacity of calcite against benzotriazole, carbamazepine, and p-CBA.…”
Section: Removal Of Micropollutants By Catalytic Ozonationmentioning
confidence: 99%
“…Zeolite catalysts exhibited an improvement in the ozonation of the pharmaceutical compound paracetamol [30] and ibuprofen [31]. Moreover, loading of the metals on zeolite catalysts increases the catalytic ozonation efficiency [32].…”
Section: Introductionmentioning
confidence: 99%